Citric acid production from pineapple waste through solid state fermentation a plant design - Battung, Elaine Joy T.; Mangaccat, Winna Faye F.; Talaro, Hanna Divine A.; Agutaya, Jonas Karl Christopher N. (Quezon City College of Engineering, University of the Philippines Diliman, 2014)
Citric acid is a naturally occurring organic acid widely used in the food, beverage and pharmaceutical industries as an additive or mild preservative. It has a worldwide demand of about three million tons and a local demand of 22,000 tons.This feasibility study for a citric acid production plant in the Philippines makes use of pineapple waste was its raw material. Pineapple waste has been chosen due to its abundance in the country. In fact, the Philippines is one of the top three pineapple producers in the world (UN Food and Agriculture Organisation, 2013). The plant is proposed to be built within PHIVIDEC Industrial Authority in the Municipalities of Tagaloan and Villanueva, Misamis Oriental. The site is near a power plant, shipping docks and the source of the major raw material. The plant has an annual target production capacity of 4,400 tons. The beverage and food industries in the Philippines are the target consumers of the product. The process for that plant may be divided into three parts: the raw materials preparation, fermentation, and separation and purification. Solid-state fermentation has been selected because the raw material is in solid form. Aspergillus niger ACM 4992 strain will be used in the fermentation process. Downstream process include filtration, evaporation, simulated moving bed (SMB) purification, crystallization, centrifugation, and drying. The use of SMB has been selected because of its reduced waste and water requirement. Moreover, it is less tedious than the usual separation techniques presently used in the industry.The analysis shows that the proposed plant is profitable with an internal rate of return of 20.74%, 2.5 times higher than the minimum acceptable rate of return (MARR) based from 8% inflation rate, and a net present value of 15.6 million US dollar or 244 million Php.
Submitted in partial fulfillment of the requirements in ChE 142 Chemical Engineering Plant Design.
Keywords: Citric acid; Citric acid industry